The effects of mindfulness and repeated cold exposure on cold tolerance and motor skill performance. (16th November 2021) - Mugford, Kaitlin; Barry, Heather; King, Michael; Ziv, Gal; Carnahan, Heather
The ability to withstand cold temperatures and perform motor tasks in cold environments is a requirement in various industries. This study aimed to determine whether being read a mindfulness passage along with repeated cold exposure could improve motor performance and tolerance in cold conditions. Participants were assigned to either a cold exposure, or a mindfulness plus cold exposure training group. For training, the cold exposure group submerged their hand in cold water (2°C), and the mindfulness group did the same as they were read a mindfulness script. Following training both groups performed a maximum duration exposure to cold test, and then performed a cold grooved pegboard and knot untying post-test. Both groups performed similarly on the motor tests. Maximum cold exposure duration was greater in the mindfulness group. Individuals exposed to cold/wet environments could increase their ability to withstand cold exposure by implementing mindfulness techniques.